2016
DOI: 10.1152/ajpgi.00435.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of innate immune activation by gluten peptide p31-43 in mice

Abstract: Celiac disease (CD) is an immune-mediated enteropathy triggered by gluten in genetically susceptible individuals. Innate immunity contributes to the pathogenesis of CD, but the mechanisms remain poorly understood. Although previous in vitro work suggests that gliadin peptide p31-43 acts as an innate immune trigger, the underlying pathways are unclear and have not been explored in vivo. Here we show that intraluminal delivery of p31-43 induces morphological changes in the small intestinal mucosa of normal mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 35 publications
4
39
0
9
Order By: Relevance
“…Thus, our results allow us to conclude that the human digestive tract has the necessary tools for gluten-protein hydrolysis. Nevertheless, different authors have indicated that gluten is not completely degraded by proteolytic gastrointestinal activity and consequently, gliadin-derived peptides such as 33-, 19- and 13-mer can accumulate and trigger inflammatory process associated with CD [8], [27]. Using partially purified extracts (ammonium sulfate-fractioned), we verified this (Figure 2).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, our results allow us to conclude that the human digestive tract has the necessary tools for gluten-protein hydrolysis. Nevertheless, different authors have indicated that gluten is not completely degraded by proteolytic gastrointestinal activity and consequently, gliadin-derived peptides such as 33-, 19- and 13-mer can accumulate and trigger inflammatory process associated with CD [8], [27]. Using partially purified extracts (ammonium sulfate-fractioned), we verified this (Figure 2).…”
Section: Discussionsupporting
confidence: 67%
“…The gliadin prolamin (from gluten) and related prolamins (from wheat, barley, and rye) are resistant to complete digestion by human digestive enzymes due to their high glutamine and proline contents. Their digestion results in the production of large peptides (10 to ≥30 amino acids) that cross the small intestinal barrier, some of which (such as 13-, 19-, or 33-mer), are capable of triggering inflammatory processes associated with CD [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such induction could explain why only limited differences between the two strains [B. longum srp ϩ and B. longum srp(Con)] were observed in this experiment. The innate immune response is a key component in the development of atrophy in CeD (30,31) and has been proposed to be involved in the pathogenesis of NCG/WS (32,33). The influx and release of neutrophil components are increased in patients with CeD (34), and by inhibiting HNE activity, Srp may specifically target a mechanism that contributes to gluten-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The colocalisation coefficient represents the weighted colocalisation coefficient of Ch1 (red) with respect to Ch2 (green) for each experiment (Araya et al, 2016;Zimmermann et al, 2014). Magnification of the micrographs was 63× objective, 2× zoom in all.…”
Section: Colocalisation Analysismentioning
confidence: 99%